Azathioprine as a therapeutic alternative for refractory chronic urticaria. (29th July 2014) - Tal, Yuval; Toker, Ori; Agmon‐Levin, Nancy; Shalit, Meir
Abstract Background Chronic urticaria (CU) affects up to 1% of the general population. Its impact on quality of life is immense, and patients might require multiple drugs to control symptoms. The main therapeutic challenge in the treatment of CU is to maintain symptomatic control while minimizing the use of glucocorticosteroids and their plethora of side effects. Methods Two patients with severe, refractory CU after treatment failure with various drugs, including high‐dose cyclosporine, were administered azathioprine. Results In both patients, the treatment with azathioprine resulted in a significant clinical improvement, enabling steroid withdrawal. Conclusion Azathioprine should be considered as a therapeutic option for chronic, steroid‐dependent urticaria, refractory to other treatments.